2020
DOI: 10.1037/pas0000816
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of the Structured Assessment of Violence Risk in Youth (SAVRY) with Indigenous and Caucasian female and male adolescents on probation.

Abstract: Indigenous people and the courts have emphasized that it is important to examine whether scores from violence risk assessment tools are valid and appropriate for Indigenous youth. However, studies are scarce. Therefore, we examined the predictive validity of youth probation officers’ Structured Assessment of Violence Risk in Youth (SAVRY) ratings for 744 Canadian youth, including 299 Indigenous youth (219 male, 80 female), and 445 Caucasian youth (357 male, 88 female) in a prospective field study. The SAVRY su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 55 publications
4
43
0
Order By: Relevance
“…1 Eight tested actuarial instruments (C. Campbell et al, 2018; Flores et al, 2016; Lowder et al, 2019; Perrault et al, 2017; Schwalbe et al, 2004, 2007; Skeem & Lowenkamp, 2016), only one of which was a pretrial risk instrument (Cohen & Lowenkamp, 2018), and three tested SPJ instruments (Lowder et al, 2019; Muir et al, 2020; Perrault et al, 2017). Four of the 10 found significant racial differences in predictive accuracy.…”
Section: What Does It Mean For An Instrument To Be Racially Biased?mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Eight tested actuarial instruments (C. Campbell et al, 2018; Flores et al, 2016; Lowder et al, 2019; Perrault et al, 2017; Schwalbe et al, 2004, 2007; Skeem & Lowenkamp, 2016), only one of which was a pretrial risk instrument (Cohen & Lowenkamp, 2018), and three tested SPJ instruments (Lowder et al, 2019; Muir et al, 2020; Perrault et al, 2017). Four of the 10 found significant racial differences in predictive accuracy.…”
Section: What Does It Mean For An Instrument To Be Racially Biased?mentioning
confidence: 99%
“…Two indicated the difference favored Black youth (C. Campbell et al, 2018; Schwalbe et al, 2004), one indicated differences were present only when gender also was considered (Muir et al, 2020), one found overprediction for Hispanic adults (Cohen & Lowenkamp, 2018), and one found overprediction for Black youth, which appeared to be a result of the criminal history items (Schwalbe et al, 2007). None of the SPJ instrument studies test bias on the structured risk judgments.…”
Section: What Does It Mean For An Instrument To Be Racially Biased?mentioning
confidence: 99%
See 1 more Smart Citation
“…A more controlled, random assignment study with a larger number of Latinx youth and JPOs is needed to better understand the differences identified for Latinx youth. Moreover, similar studies of youth from additional racial and ethnic groups that are representative of different juvenile justice populations are needed and are slowly increasing (e.g., Muir et al, 2020). Despite the limitations of the research design, an obvious benefit of this study that cannot be understated is its generalizability to actual probation practice.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, research has demonstrated risk ratings have equivalent predictive accuracy (as measured by comparing the area under receiver operator characteristic curves) or are equivalent in the functional form of their association with recidivism or violent behavior (as measured by an absence of a Race × Risk interaction in regression models, for example; Skeem & Lowenkamp, 2016) across racial and cultural groups. Studies of SPJ instruments have documented this equivalent prediction of outcomes between White individuals and Black youth (SAVRY; Perrault et al, 2017; Vincent et al, 2011), Hispanic youth (SAVRY, Vincent et al, 2011), Indigenous youth (Muir et al, 2020), Black adults (START, Lowder et al, 2019), and non-Caucasian adults (HCR-20V2, O’Shea et al, 2014). Moreover, using HCR-20 total risk scores created for research purposes, researchers have reported equivalent predictive accuracy for recidivism between White and Black adults (Snowden et al, 2010), and equivalent predictive accuracy for inpatient violence between White, Asian and Hawaiian adults on the HCR-20 (Fujii et al, 2005).…”
Section: Risk Assessment Instruments and Racial Biasmentioning
confidence: 97%